Influence of religious orientation on Jordanian viewers’ loyalty towards satellite TV channels - Abu-Alhaija, Ahmad Saifalddin (2018)
A review of the literature shows that few studies investigated customer’s loyalty model from a religious perspective. In addition, most of these studies investigated the religious influences on customer’s loyalty model using two religious dimensions, namely religious commitment and religiosity. Therefore, this study examined the influence of religious orientation (the motivational approach of religion), as another religious dimension, on a) viewer’s loyalty, b) viewer’s satisfaction, and c) perceived content quality. The influences of the perceived content quality, as well as, viewer’s satisfaction on viewer’s loyalty were examined. The mediating roles of both viewer’s satisfaction and perceived content quality were also examined. A total of 750 Jordanian viewers were invited to participate in this study. Survey questionnaires were distributed in the urban areas of Amman and Irbid. This study managed to obtain 644 valid responses. Structural equation modelling (SEM) using AMOS was then used to test eight hypotheses constructed from the conceptual framework of the study. SEM analysis revealed that: a) religious orientation has a direct positive influence on viewer’s loyalty, viewer’s satisfaction, and perceived content quality; b) perceived content quality has a direct positive influence on viewer’s satisfaction; c) viewer’s satisfaction has a direct positive influence on viewer’s loyalty; d) perceived content quality does not have any direct influence on viewer’s loyalty. On the other hand, perceived content quality has a partial mediation role in the relationship between religious orientation and viewer’s satisfaction. In contrast, viewer’s satisfaction has a full mediation role in the relationship between perceived content quality and viewer’s loyalty. Theoretically, the proposed framework of the study provided important contributions to the literature of consumer behaviour. This study provided a useful model to better understand loyalty relationships through the motivational approach of religion. Findings of the study could benefit the decision makers of satellite TV channels in order for them to determine the effective polices to enhance perceived content quality, viewer’s satisfaction, and viewer’s loyalty.